A Case Study of Nalgonda Rainfall, Temperature and Climatic and Its Effect on Agricultural Productivity: Understanding the Impact of Climatic Changes on Agricultural Productivity: A Case Study in Nalgonda Region (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Climates have changed before and will continue to change over later on. Alongside crustal development of the earth surface, climatic changes will undoubtedly be prove because of cumulative effect of earthbound and additional earthly forces. Eustatic and isostatic effects of such changes were dependably felt on the huge geo forms and along these lines on the land use frameworks. The biggest known financial effect of environmental change is upon horticulture as a result of the size and affectability of the area. Warming makes the best mischief horticulture in creating nations fundamentally in light of the fact that numerous homesteads in the low latitudes as of now suffer climates that are excessively hot. This paper audits several examinations that measure the span of the effect of warming on ranches in Nalgonga District in Telangana State. The most powerless segment to environmental change is horticulture and rural productivity would be significantly influenced by even a slight change in climatic condition. Horticulture is most vulnerable to climatic change when contrasted with different parts like water assets, timberlands and other the effect biological systems. The present examination has been attempted Nalgonda area to analyze the effect of changes in rainfall and temperature on the horticultural productivity at the mandalregion level in this locale of Telangana. The examination included factual assessment of rainfall, temperature and other meteorological parameters for a time of ten years.